2001
DOI: 10.1006/jmbi.2000.4203
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of a liganded trehalose/maltose-binding protein from the hyperthermophilic archaeon Thermococcus litoralis at 1.85 Å

Abstract: We report the crystallization and structure determination at 1.85 A Ê of the extracellular, membrane-anchored trehalose/maltose-binding protein (TMBP) in complex with its substrate trehalose. TMBP is the substrate recognition site of the high-af®nity trehalose/maltose ABC transporter of the hyperthermophilic Archaeon Thermococcus litoralis. In vivo, this protein is anchored to the membrane, presumably via an N-terminal cysteine lipid modi®cation. The crystallized protein was N-terminally truncated, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 56 publications
4
92
0
Order By: Relevance
“…trehalose/maltose-binding protein and cyclo/maltodextrin-binding proteins) from other sources have also been determined (33,(45)(46)(47) (49), and liganded open (50) states have been reported. In the case of GL-BP, we could not obtain crystals without ligands even after extensive crystallization screening.…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
“…trehalose/maltose-binding protein and cyclo/maltodextrin-binding proteins) from other sources have also been determined (33,(45)(46)(47) (49), and liganded open (50) states have been reported. In the case of GL-BP, we could not obtain crystals without ligands even after extensive crystallization screening.…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
“…In early studies the trehalose-maltose-binding protein (TMBP) was identified, and transport was shown to occur with a very high affinity of 20 nM at 80 • C (Xavier et al, 1996). Later TMBP and MalK, the ATPase domain of this transporter, were crystallized (Diederichs et al, 2000;Diez et al, 2001;see below). Finally, the entire transporter was heterologously expressed in E. coli and purified .…”
Section: Introductionmentioning
confidence: 99%
“…In the open state, the substrate can interact with the binding site whereupon the two domains come together forming a closed state in which the substrate is occluded. The three-dimensional structure of the catalytic site of both Tl-TMBP (PDB-entry: 1EU8) and Pf-MDBP (PDBentry: 1ELJ) has been solved with bound substrate [7,10]. Although both proteins are structurally similar to the E. coli MalE, some differences can be observed.…”
Section: Binding Proteinmentioning
confidence: 99%
“…The dissociation constants vary between 40 and 500 nM [1,16] (Table 3). With Tl-TMBP, substrate binding appears to be fast, whereas substrate dissociation is slow and temperature dependent [7,14]. These latter features might be due to the more excessive interactions of the substrate with the binding protein.…”
Section: Binding Proteinmentioning
confidence: 99%